Pengaruh Karakteristik Pekerjaan dan Kompetensi terhadap Kinerja Pegawai Serta Peran Dukungan Organisasi yang Dirasakan Sebagai Variabel Moderasi : Studi pada Guru SMA Kristen Waibakul, Sumba Tengah - Ignasius Kaledi Lelak (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
The purpose of this study was to determine the effect of job characteristics and competencies on employee performance and the role of perceived organizational support as a moderating variable (Study on Waibakul Christian High School Teachers, Central Sumba). The independent variables in this study consisted of job characteristics variables (X1) and job competency variables (X2). The dependent variable was employee performance (Y), and perceived organizational support as a moderating variable (M). This type of research is quantitative research, using descriptive analysis and path analysis.